INCREASING STUDENTS VOCABULARY MASTERY BY USING MNEMONIC TECHNIQUE ON TENTH GRADE AT SMK NU PACE - Lusiana Afrilia; Caltira Rosiana (Universitas PGRI Mpu Sindok, 2025)
In learning vocabulary, students tend to have difficulty in memorizing or remembering vocabulary in English, this makes it difficult for students to understand or receive information . To be fluent in English, students must master vocabulary as well as possible. The aims of this study is to find out the significant differences between students outcomes that learn with and without mnemonic technique at SMK NU Pace. This research design uses quantitative and the type of research uses quasi-experimental with a static group comparison model. The analysis technique used to analyze the data in this study is descriptive statistics and inferential statistics using the t-test. Based on the posttest scores, students who learned using mnemonic techniques got an average score of 86.42 while students who learned without using mnemonic techniques got an average score of 55. Then based on the calculation of a significant level of 5% for Df = 27, the value of tcount = 7.297 and ttable = 1.703 then tcount> ttable so that Ha is accepted. Based on the results of these calculations, it seen that “There is a significant difference in the vocabulary mastery of students who use mnemonic techniques with those who do not use mnemonic techniques”.